A Qualitative Exploration of Weight Bias and Quality of Health Care Among Health Care Professionals Using Hypothetical Patient Scenarios - Seymour, Justine; Barnes, Jennifer L.; Schumacher, Julie; Vollmer, Rachel L. (Inquiry (Chicago), 2018)
The purpose of this study was to determine whether weight bias exhibited by health care professionals (HCPs) impacts quality of health care provided to individuals with obesity. HCPs (n = 220; 88% female, 87% nurses) in the Midwest region of the United States were recruited to complete an online survey. In this within-subjects study design, participants completed the Attitudes Towards Obese Persons (ATOP) scale to assess weight bias and responded to 2 (1 person with obesity and 1 person without obesity) hypothetical patient scenarios to evaluate quality of care. A median split was calculated for ATOP scores to divide participants into high or low weight bias groups. Within these groups, thematic analysis was used to uncover themes in quality of care based on participants’ responses to each scenario. The analysis revealed that HCPs in the high weight bias group gave specific diet and exercise recommendations, offered health advice regarding weight loss, and used less teaching discourse when responding to the patient with obesity. In addition, in both weight bias groups, patients with obesity were started on pharmaceutical therapies sooner. The findings of this study suggest a need to educate HCPs on the importance of empathy and compassion when providing treatment to all patients, regardless of weight, to increase quality of care and ultimately improve patient outcomes.